MOTIVASI BELAJAR KIMIA TERHADAP KEMAMPUAN KOGNITIF PESERTA DIDIK PADA MATERI SISTEM KOLOID - TUMINAH, MARIA LUCIA; LARASATI, CHRISTIANA NIKEN; MURTIHAPSARI, MURTIHAPSARI (Jurnal Ilmu Pendidikan Indonesia, 2021)
Education can be created through an active learning atmosphere in developing the self-potential of students to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. This study aims to determine the influence and relationship between motivation to learn chemistry on cognitive learning outcomes of students at SMA Negeri 1 Manokwari on colloidal system material. The research method used is a quantitative experiment with an associative approach. This research design used pre-experimental design in the form of One-Shot Case Study. The sampling technique in this study used the Non Probability Sampling Technique, with Purposive Sampling. The samples used were students. Data collection instruments included a questionnaire on motivation to learn chemistry and tests of cognitive learning outcomes. The results showed that there was a significant influence between the motivation to learn chemistry on students' cognitive learning outcomes, which was indicated by the significance value obtained from the simple linear regression test and the correlation test, namely 0.0001 and the R Square value of 33%. and there is a positive relationship between motivation to learn chemistry on cognitive learning outcomes of students.